PENGEMBANGAN VIDEO PEMBELAJARAN ILMU PENGETAHUAN SOSIAL BERBASIS STUDENT CENTERED LEARNING - Susanto, Susanto; Jaenuddin, Riswan; Basir, M. Djahir (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2022)
This study aims to develop a Student-Centered Learning (SCL) based learning video on Social Science subjects at the Raudhatul Ulum Integrated Islamic Junior High School that is valid, practical, and effective on student learning outcomes. This research is a development research using the Hannafin Peck model. Data collection techniques used in this study were interviews, walkthroughs, questionnaires, and tests of student learning outcomes against the developed video media. This research was declared valid because it was obtained through a validation process from experts. For practicality obtained from student responses at the small group stage obtained by 65.5% indicating that this multimedia has been tested for practicality because the video media produced is attractive to students, easy to understand, and students master the competencies to be achieved faster, while the effectiveness of student learning outcomes seen from the results of the N-gain 0.36 in the medium category. Based on the results of the study, it can be concluded that the video media based on student centered learning that was developed proved to be valid, practical, and effective on student learning outcomes.